Malaysian Medical Students' Career Intention (MMSCI): a cross-sectional study - Zhi Sean Teng; Gerald Tze Zhen Ser; Wei-Han Hong; Chin Hai Teo; Yang Faridah Abdul Aziz; Jamunarani Vadivelu; Malaysia MedEd Collaborative (BMC, 2024)
Abstract Background In recent years, there have been many instances of negative sentiments expressed by and resignations observed from doctors working in the Ministry of Health (MOH), Malaysia. However, little is known about the perspectives of medical students and their career intentions. This study aims to determine the current Malaysian medical students' career intentions immediately after graduation and upon completing the 2 years of housemanship and to establish the factors influencing these intentions. Methods This was a cross-sectional study of 859 Malaysian medical students from 21 medical schools who voluntarily completed a self-administered online questionnaire that was disseminated by representatives from medical schools nationwide and social media platforms of a national medical student society. Results 37.8% of the respondents were optimistic about a career with the Ministry of Health (MOH), Malaysia in the future. Most of the respondents (91.2%) plan to join and complete the MOH Housemanship programme as soon as possible after graduation, with the majority of them (66.2%) planning to complete it in their state of origin. After 2 years of Housemanship programme, only more than half of the respondents (63.1%) plan to continue their careers in MOH. Slightly more than a quarter (27.1%) of the total respondents plan to emigrate to practise medicine, with 80.7% of them planning to return to Malaysia to practise medicine after some years or after completing specialisation training. Combining the career intentions of Malaysian medical students immediately after graduation and upon completion of the 2 years housemanship programme, only a slight majority (57.5%) of the respondents plan to continue their career in MOH eventually. Most of the respondents (85.0%) intend to specialise. Conclusion A concerning number of Malaysian medical students plan to leave the Ministry of Health workforce, the main healthcare provider in Malaysia, in the future. Urgent government interventions are needed to address the underlying factors contributing to the potential exodus of future doctors to prevent further straining of the already overburdened healthcare system, posing a significant threat to public well-being. An annual national study to track medical students' career intentions is recommended to gather crucial data for the human resources for health planning in Malaysia.